Computation of Metric-Based Resolvability of Quartz Without Pendant Nodes - Ali N. A. Koam (IEEE, 2021)
Silica comes in three different crystalline forms, with quartz being the most common and plentiful in the crust of our planet. Other variations are created when quartz is heated. Each chemical structure may be deduced from graphs in which atoms alternate as vertices and edges as bonds, according to chemical graph theory. The latest advanced topic of resolvability parameters of a graph is, where the complete topology is formed in a particular way that every single atom’s unique location is obtained. The resolving basis, edge resolving basis, and some generalizations were investigated in this paper as resolvability characteristics of Quartz. Understanding and dealing with structures is made easier by transforming the entire topology into a unique form given by resolvability parameters.